2012
DOI: 10.3126/kumj.v9i1.6264
|View full text |Cite
|
Sign up to set email alerts
|

Ocular trauma in patients presenting to Dhulikhel Hospital

Abstract: Background Ocular trauma is an important cause of blindness and ocular morbidity throughout the world. Prevalence studies help to define the target group, plan strategies and thereby lessen trauma related blindness in the country. Objective To identify the risk factors for ocular trauma, those at risk, describe the visual acuity at time of clinical presentation, and assess the nature and severity of ocular trauma in patients presenting to Dhulikhel Hospital’s emergency department and eye OPD with ocular trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 7 publications
5
20
1
Order By: Relevance
“…In contrast, previous series in Nepal have demonstrated monocular blindness in only 5–10% of patients on follow-up [8], even when presentation was delayed [13], reflecting the greater severity of injuries in the current series. Blindness may be devastating for an individual, with loss of vision in one or both eyes being classified as a 24% or 85% whole person impairment respectively [17].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In contrast, previous series in Nepal have demonstrated monocular blindness in only 5–10% of patients on follow-up [8], even when presentation was delayed [13], reflecting the greater severity of injuries in the current series. Blindness may be devastating for an individual, with loss of vision in one or both eyes being classified as a 24% or 85% whole person impairment respectively [17].…”
Section: Discussioncontrasting
confidence: 71%
“…Corneal trauma leading to ulceration is the second most common cause of monocular blindness after cataract in Nepal. Major causes of ocular trauma in Nepal include agricultural and domestic work, road traffic accidents and physical assault [8]. Although there have been many reports describing ocular trauma in Nepal [6, 8–13], little is known about the burden of ocular trauma during the recent earthquakes in Nepal or burden due to other such natural disasters around the world.…”
Section: Introductionmentioning
confidence: 99%
“…7,9 But other studies observed that most ocular injuries occurring during household activities. 1,2,6 71.8% of patients in this study presented in to the eye specialist within 48 hours after injury, 15.8% in between 48 hours -1 week while 12.4% presented after 1 week duration. Study at Dhulikhel also has reported that 54.5% patients presented within a day.…”
Section: 7mentioning
confidence: 67%
“…However wood stick was found to be most common object of injury in other studies. 6,11,12 In this study it was observed that out of 209 patients, only 5 patients gave history of wearing protective devices while working. It is believed that with education about use of proper eye protection, 90% of eye injuries could be prevented.…”
Section: 7mentioning
confidence: 83%
See 1 more Smart Citation